Design perspectives on 22nm CMOS and beyond - Borkar, Shekhar (2009 46th ACM/IEEE Design Automation Conference, 2009)
This paper presents technology and economic challenges posed by 22nm CMOS and beyond, and how they can be addressed by advances in design technology, validation, and testing, to exploit the benefits of scaling we have enjoyed over the decades.